The molecular basis of Gs protein efficacy at the b2- adrenoceptor - Harwood, Clare (2022)
GPCRs are the largest family of transmembrane receptors in the human genome and currently represent 34% of all FDA approved medicines. The β2-adrenoceptor (β2AR) is a prototypical class A GPCR which is therapeutically relevant in asthma, whereby β2AR agonists relieve bronchoconstriction. Despite the therapeutic importance of the β2AR and other GPCRs the molecular basis of agonist efficacy is not well understood.